2022
DOI: 10.3390/agronomy12030649
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil Composition and Bioactive Properties of Lemon Balm Aerial Parts as Affected by Cropping System and Irrigation Regime

Abstract: The ongoing climate crisis necessitates the sustainable use of natural resources and the adoption of environmentally friendly agronomic practices. Deficit irrigation is an ecofriendly technique that allows for the improvement in the water use efficiency of crops. On the other hand, medicinal and aromatic crops, which usually have an innate tolerance to harsh conditions, are suitable candidates for cultivation under low-input cropping systems. In the present study, Melissa officinalis plants were cultivated und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Lemon balm farming is stimulated by the remarkable low essential oil output, which, on average, is 0.1%, while cultivation yields approximately five metric tons of the dried material per hectare [ 7 ]. The largest world producers are Egypt, Turkey, the United Kingdom, and the United States [ 8 ]. Poland’s production is among the largest in Europe and approaches 1500 tons annually [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lemon balm farming is stimulated by the remarkable low essential oil output, which, on average, is 0.1%, while cultivation yields approximately five metric tons of the dried material per hectare [ 7 ]. The largest world producers are Egypt, Turkey, the United Kingdom, and the United States [ 8 ]. Poland’s production is among the largest in Europe and approaches 1500 tons annually [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thymus species are exceptional case studies in chemodiversity domains, as over 20 chemotypes have already been described for their EO profiles [ 37 ]. To date, several studies have shown that the phytochemical constituents of plant species can be altered due to agronomic practices [ 38 ], natural diversity [ 39 ], intra- or inter- specific variations [ 4 , 40 ], abiotic stresses [ 41 ], elicitor applications [ 42 ], and site-directed mutagenesis in corresponding enzymes [ 43 ]. In another study, Vaičiulytė & Ložienė stated that even meteorological factors can significantly influence the amounts of phenolic and non-phenolic monoterpenes in three chemotypes of Thymus pulegioides [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The difference in dry matter content between peppermint and lemon balm was as much as 13.18 g/100 g. Similar differences between mint and lemon balm are presented by the results of Kaur et al [29]; in this case, the difference was 14.5 g. Similar results of dry matter content for peppermint were achieved in the studies of Uribe et al [30] (27.5%). In turn, Chrysargyris et al [31], on the first date of harvesting lemon balm, provided the DM content in the range of 21.06-24.48% and emphasized that it depended on the method of cultivation and irrigation of the crop. The dry matter content results presented in this study are much higher, which may be related to the plant development phase [24], as well as the use of other varieties and climatic conditions.…”
Section: Discussionmentioning
confidence: 99%